Foundations of decision analysis - Howard, Ronald A. 1934-; Abbas, Ali E. (Ali El-Sayed) (Always learning., 2016)
The book treats decision making as an evolutionary process from a scientific standpoint. Strategic decision-making analysis is presented as a tool to help students understand, discuss, and settle on important life choices. Through this text, students will understand the specific thought process that occurs behind approaching any decision to make easier and better life choices for themselves.